Effects Of Radiation, Chemical Reaction And Viscous And Joule Dissipations On Mhd Nanofluid Flow And Heat Transfer Past A Stretching Sheet With Melting - S. B. Padhi, S. Das, G. K. Mahato (International Journal of Modern Agriculture, 2020)
An investigation is done to analyze the Effects of Radiation, Chemical Reaction and Viscous and Joule Dissipations on MHD Nanofluid Flow and Heat Transfer past a Stretching Sheet with Melting in the presence of a uniform transverse magnetic field applied parallel to the stretching sheet. The governing nonlinear partial differential equations are transformed to a set of nonlinear ordinary differential equations which are then solved numerically using Matlab’s inbuilt method bvp4c. The behavior of emerging parameters is presented graphically and discussed for velocity, temperature, and nanoparticles volume fraction. Numerical values of skin friction, rate of heat transfer, and rate of mass transfer at the plate are presented in tabular form, for various values of pertinent flow parameters.